POTENTIAL GROUPER FEED FORMULATION BASED ON EVOLUTIONARY ALGORITHM CONCEPT WITH A UNIQUE SELECTION OPERATOR - Soong, Cai Juan; Ramli, Razamin; Abd. Rahman, Rosshairy (2018)
The problems of insufficient wild catch grouper fish and the high demand in the market have increased the need of farming the grouper fish. In order to farm the grouper fish, there is a need to have abundant of trash fish as their feeds since grouper fish is a carnivorous fish. But, trash fish is dramatically expensive and hard to store, hard to maintain the quality of nutrients as well as the quantity throughout the years. Therefore, turning to formulated feed mix is the alternative. However, the issue is on its cost while providing quality feed mix. That leads to the search for an approach which could provide the most suitable feed ingredients and nutrients. One potential approach is the Evolutionary Algorithm (EA) which has been used to solve the feed formulation problems in poultry, shrimp and cattle. Hence, in this study, an EA-based approach with a refinement on using the standard deviation in the strategy of tournament selection has been proposed to minimize the total cost in formulating the feed of grouper fish. Results show that the lowest cost can be accepted while satisfying the nutrient requirements of grouper fish